2006
DOI: 10.1897/05-234r.1
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic endpoints in fish early life‐stage tests: Luciferase and vitellogenin induction in estrogen‐responsive transgenic zebrafish

Abstract: This study incorporated specific endpoints for estrogenic activity in the early life-stage (ELS) test, as described in Guideline 210 of the Organization for Economic Cooperation and Development and traditionally used for toxicity screening of chemicals. A transgenic zebrafish model expressing an estrogen receptor-mediated luciferase reporter gene was exposed to ethinylestradiol (EE2), and luciferase activity as well as vitellogenin (VTG) was measured. Concentrations of EE2 were tested at 1, 3, or 10 ng/L for 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 33 publications
(50 reference statements)
2
17
0
Order By: Relevance
“…Bogers et al (2006) found no negative influence on mortality, development and length growth of transgenic zebrafish (Danio rerio) in the early life stages when exposed over However, a significant positive effect on weight growth was observed (35% compared to the control). Although not significantly different, a 12% higher mean weight of fish exposed to the lowest concentration (0.2 ml·l -1 ) of DMSO, compared to the control group was found in the current study.…”
Section: Discussionmentioning
confidence: 79%
“…Bogers et al (2006) found no negative influence on mortality, development and length growth of transgenic zebrafish (Danio rerio) in the early life stages when exposed over However, a significant positive effect on weight growth was observed (35% compared to the control). Although not significantly different, a 12% higher mean weight of fish exposed to the lowest concentration (0.2 ml·l -1 ) of DMSO, compared to the control group was found in the current study.…”
Section: Discussionmentioning
confidence: 79%
“…This assay has been performed using adult zebrafish and juveniles (30 dpf). The latter, which are at the stage of gonad differentiation, appear to be more responsive (Legler et al 2000, Legler et al 2002, Bogers et al 2006. In addition, two transgenic zebrafish lines have been generated in which GFP is used, enabling microscopic analysis of the reporter activity.…”
Section: Figurementioning
confidence: 99%
“…In these lines, an Er-responsive promoter is genetically fused to a reporter gene encoding either luciferase or GFP. Using a transgenic line with the luciferase gene coupled to a promoter with a single estrogen response element (ERE), Er activity could be measured after 96 hour exposure to estrogens by measuring the luciferase activity in tissue homogenates [17,30]. This assay has been performed using adult zebrafish and juveniles, in which adults appear to be more responsive.…”
Section: The Zebrafish Ersmentioning
confidence: 99%